Penerapan Algoritma Rule Base dengan Pendekatan Hexadesimal pada Transliterasi Aksara Bima Menjadi Huruf Latin - Arik Aranta; Fitri Bimantoro; I Putu Teguh Putrawan (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
Aksara Bima is a text-based information exchange media that has never been lost. At this time the Bima script began to be studied again indicated, with researchers who began to explore the history and stages of the process of digitizing the characters including the Bima script. Thus providing hope for the use of characters in community activities. One problem faced when wanting to learn the characters felt by the community is the different forms of characters in Latin letters and there are fixed rules when writing characters that make the process of writing characters feel difficult. So the writing of characters in daily activities in community activities still cannot be said to be massive due to these problems. In this study, the writer will develop an algorithm that can facilitate the learning activities of characters, which is specialized in the process of reading the Bima Script. The method adopts the concept of machine learning that is applied to the process of transliteration of Bima, into Latin letters. With a string replacement algorithm that is optimized by using hexadecimal numbers. The results obtained from this transliteration process in the form of system accuracy that reaches 90.64% of 171 implemented rule base.